Enablers and deterrents on the school-based condom availability and distribution: a scoping review - Mark Donald C Reñosa; Tricia Kaye F. Palola; Carl Abelardo T. Antonio (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background In an effort to decrease teenage pregnancies and sexually transmitted diseases, there are discussions on the implementation of a school-based condom availability and distribution policy. However, there is a dearth of information on the extent and range of the empirical evidence supporting this policy initiative. Hence, this study aimed to identify enablers and deterrents of the program to serve as groundwork for health professionals and policy makers toward a more comprehensive adolescent program in the country. # Methods A scoping review of literature based on the five-stage framework by Arskley and O'Malley was utilized in the study. Two researchers performed a comprehensive search of peer-reviewed literature through PubMed, ScienceDirect, EBSCOhost and ProQUEST published from 1985 to 2016. Inclusion criteria for records were: i) Original research published in a peer-reviewed journal; ii) Focused on school-based condom availability and distribution; iii) Study participants were students in a secondary public or private schools; iv) Published in English language. Two researchers independently appraised each record against the set inclusion criteria. Likewise, independent abstraction of data from selected studies were performed. Disagreements in screening, selection, and abstraction were settled through consensus. # Results A total of 2,114 records were initially screened for eligibility, of which eight met the inclusion and exclusion criteria. Seven of the studies were conducted in the USA and one study was carried-out in Mexico. Notably, none of the published papers originated in Asia. Four essential themes emerged that reinforces the program: i) establishment of state-level policy; ii) engagement of stakeholders and parents on public dialogue: iii) empowering activities in schools; and iv) increasing condom reach and coverage. On the other hand, four significant barriers were recognized; i) assumption that condom availability and distribution to adolescents promote sexual promiscuity; ii) lack of parental support due to religious and moral concerns and the acceptance of the students to certain programs; iii) discomfort and embarrassment felt in general by the students towards acquiring condoms in schools; and iv) structural barriers such as poor coverage and gender differences among male and female students. # Conclusions These findings suggest that there have been limited studies conducted on the success and challenges of school-based condom availability program. Although study results have shown substantial benefits of the program, emergence of thematic insights relating to parental support, sexual attitude and behavior, program coverage and structural implications acted as major enablers and deterrents on condom availability and distribution program. It is crucial to recognize these existing issues to generate strategic recommendation and action for improvements of the program.